2021
DOI: 10.4067/s0718-34292021000100093
|View full text |Cite
|
Sign up to set email alerts
|

Insecticidal potential of physic nut fruits of different stages of maturation on Myzus persicae (Hemiptera: Aphididae)

Abstract: Potencial insecticida de frutos de piñón manso en diferentes etapas de maduración sobre Myzus persicae (Hemiptera: Aphididae

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Important factors that may have influenced the mortality of the mites are the plant part from which the secondary compounds were extracted and the form of application of the extract. Most of the plant's defense mechanisms are concentrated in the seeds, given their great importance as a vehicle for the propagation and survival of the species [13] . The higher or lower concentration of these compounds is generally determined by exogenous factors such as light, precipitation, place of cultivation, spacing, and sun, as well as by endogenous factors such as plant age and genetic variability in populations [14] .…”
Section: Discussionmentioning
confidence: 99%
“…Important factors that may have influenced the mortality of the mites are the plant part from which the secondary compounds were extracted and the form of application of the extract. Most of the plant's defense mechanisms are concentrated in the seeds, given their great importance as a vehicle for the propagation and survival of the species [13] . The higher or lower concentration of these compounds is generally determined by exogenous factors such as light, precipitation, place of cultivation, spacing, and sun, as well as by endogenous factors such as plant age and genetic variability in populations [14] .…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported the effect of green fruit seed extracts and seed oils from fresh and dry fruits of J. curcas on adult green aphids Myzus persicae (S.) (Homoptera: Aphididae). Cabbage leaves (B. oleracea (L.) treated with 0.0, 0.5, 1.0, 1.5, 2.0, 2.5, and 3.0% (w/v) of the extract in an ingestion bioassay were tested, with 61 and 71% mortality after 48-72 h at 2.5% [67].…”
Section: Homopteramentioning
confidence: 99%